A Note on exchange rate pass-through in CIS countries - Iikka Korhonen; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
We assess the extent and speed of exchange rate pass-through in the countries of the Commonwealth of Independent States (CIS).We do this in the framework of vector autoregressive regressions, utilising impulse functions and variance decompositions with monthly data that starts in 1999 in order to avoid periods of very high inflation and the Russian crisis.We find that exchange rate movements have a clear impact on price developments in the CIS countries.The speed of the pass-through is also fairly high: in most cases the full effect is transmitted into domestic prices in less than 12 months.Unlike in many other emerging market economies, an additional effect from US prices on to domestic prices is not significant.The extent of the exchange rate pass-through is usually much higher than in our benchmark group of emerging market countries.Variance decomposition shows that the relative share of exchange rates in explaining changes in domestic prices is higher in the CIS countries than in the benchmark group. Our results indicate that policy-makers in the CIS countries need to pay more attention to exchange rate movements than in many other emerging market countries.
URN:NBN:fi:bof-201408072136
Keywords: E31; E42; F31; F42; 330; exchange rate pass-through; inflation; exchange rate regime; transition countries